2021
DOI: 10.1038/s41535-021-00364-z
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous and anisotropic nonlinear susceptibility in the proximate Kitaev magnet α-RuCl3

Abstract: The leading order nonlinear (NL) susceptibility, χ3, in a paramagnet is negative and diverges as T → 0. This divergence is destroyed when spins correlate and the NL response provides unique insights into magnetic order. Dimensionality, exchange interaction, and preponderance of quantum effects all imprint their signatures in the NL magnetic response. Here, we study the NL susceptibilities in the proximate Kitaev magnet α-RuCl3, which differs from the expected antiferromagnetic behavior. For T < Tc = 7.5 K a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Another experiment has indicated multiple phase transitions in the same field region based on the anomalies in thermal (both longitudinal and Hall) conductivity [63] Evidence of magnetic excitations [64] and phonon anomlies [65] are also presented in experiments in the same field region (before polarized phase appears). More interestingly, this is roughly the same magnetic field region where a recent experiment finds a signature of glassiness [20].…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Another experiment has indicated multiple phase transitions in the same field region based on the anomalies in thermal (both longitudinal and Hall) conductivity [63] Evidence of magnetic excitations [64] and phonon anomlies [65] are also presented in experiments in the same field region (before polarized phase appears). More interestingly, this is roughly the same magnetic field region where a recent experiment finds a signature of glassiness [20].…”
Section: Introductionsupporting
confidence: 53%
“…Spin glasses, both classical and quantum, are often found in systems with spatial disorder. In an exciting recent experiment, glassiness is found in a nearly disorderfree α-RuCl 3 at low temperatures and intermediate magnetic fields [20], as seen in anomalous non-linear susceptibilities. Is α-RuCl 3 , a Kitaev proximity system, showing us a way to intrinsic glassiness in disorder-free and generic quantum spin liquid systems?…”
Section: Introductionmentioning
confidence: 97%
“…Very recently the 2DCS of one-dimensional Ising model has been investigated by implementing matrix-product state numerical simulations 60,61 . Nonlinear responses of KM in the context of high-harmonic generation (HHG) has been studied theoretically 62 and anomalous behavior of the Kitaev spin liquid candidate α-RuCl 3 for static nonlinear susceptibilities has also been reported 63 . It has been shown that the anyonic statistic of quasiparticles can be revealed by nonlinear pumpprobe spectroscopy 64 .…”
Section: Introductionmentioning
confidence: 99%